"This Can Be a Powerful Tool": Peer Sexuality Education during the COVID-19 Pandemic. Issue 2 (3rd April 2022) - Bowling, Jessamyn; Glenn, Mary-Lynn; Davis, Cameron; Dinkins, Heather; Mabe, Gerald Branden; Williams, Cody
Abstract: The COVID-19 pandemic has resulted in shifts in college education and subsequently peer sexuality education for college students. We examine one case study of a peer sexuality education group's challenges and benefits of navigating from in-person to online sexuality education work. We include reflexive journal entries from past and current members ( n = 5), a survey from past and current members ( n = 4), and organizational artifacts. We find challenges from both the peer education work itself and within the organization as well as benefits of accessibility and addressing marginalized topics in online spaces. Our findings suggest that future virtual peer education may require strong infrastructure and virtual education skills.